Conductivity studies of PEO- LiBF4- EC polymer electrolytes / Mohamad Hanif Mohamad Taib - Mohamad Taib, Mohamad Hanif (2008)
In this work, PEO is used as a polymer host while lithium tetrafluroburate (LiBF4) as the doping salt to prepare dry polymer electrolytes systems by using solution casting technique. The ionic conductivity was investigated with the additional concentration of salt. PEO-LiBF4 polymer electrolytes with highest ionic conductivity were used for preparing plasticized polymer electrolytes (PEO-LiBF4-EC) with different concentration of EC added as plasticizer. The ionic conductivity of plasticizer polymer electrolytes was studied. Ionic conductivity values in the order of 10"4 or 10"5 Scm"1 were obtained from the PEO-LiBF4-EC system.